CFTR controls biliary epithelial inflammation and permeability by regulating Src tyrosine kinase activity - Fiorotto, Romina (Hepatology, 2016)
In the liver, CFTR regulates bile secretion and other functions at the apical membrane of biliary epithelial cells (i.e cholangiocytes). CF-related liver disease (CFLD) is a major cause of death in patients with CF. CFTR dysfunction affects innate immune pathways, generating a para-inflammatory status in the liver, and other epithelia. This study investigates the mechanisms linking CFTR to TLR4 activity. We found that CFTR is associated in a multi-protein complex at the apical membrane of normal mouse cholangiocytes, with proteins that negatively control Src activity. In CFTR-defective cholangiocytes, Src tyrosine kinase self-activates and phosphorylates TLR4, resulting in activation of NF-κB, and increased pro-inflammatory cytokines production in response to endotoxins. This Src/NF-κB-dependent inflammatory process attracts inflammatory cells, but also generates changes in the apical junctional complex and loss of epithelial barrier function. Inhibition of Src decreased the inflammatory response of CF-cholangiocytes to LPS, rescued the junctional defect in-vitro and significantly attenuated endotoxin-induced biliary damage and inflammation in vivo (Cftr-KO mice). CONCLUSION: Our findings reveal a novel function of CFTR as regulator of TLR4 responses and cell polarity in biliary epithelial cells. This mechanism is pathogenetic, as shown by the protective effects of Src inhibition in vivo and maybe a novel therapeutic target in CFLD and other inflammatory cholangiopathies.